ASSOCIATION OF EDUCATION AND HOUSING QUALITY WITH PUBLIC HEALTH EVENTS OF NATIONAL SIGNIFICANCE IN EIGHT MUNICIPALITIES OF CALDAS - COLOMBIA - Gonzalez, Ricardo; Bermont, Gerson; CárdenasAlzate, Pedro Pablo (International Journal of Engineering Technologies and Management Research, 2021)
A questionnaire called “Family sheet” was created to collect information about the population of the Department of Caldas – Colombia. Method: Analytical cross-sectional study using information from these questionnaires and the Colombian National System of Public Health Surveillance Results: A total of 1735 public health events of national significance were found. The most common levels of education were “secondary education” and “Pre-school or primary education”. Most of the dwellings had “safe and adequate water supply”, “sanitary disposal of excreta”, adequate “structural features and furnishing”, and “appropriate “lighting”. Their “disposal of solid wastes, and personal and domestic hygiene” was fair and they did not have “indoor air pollution” or “Overcrowding”. Statistically significant associations were found of some levels of education with chickenpox, zika virus disease, foodborne diseases, external causes of injuries and fluoride exposure. They were also identified between “safe and adequate water supply” and/or “sanitary disposal of excreta” and dengue, chikungunya y leishmaniasis; “structural features and furnishing” and fluoride exposure, and “Overcrowding” and Violence against women, domestic and sexual violence/gender-based violence. However, the predictive value of these variables was weak. Conclusions: The distribution of studied variables was similar to previous studies and some statistically significant associations were found; however, their predictive value was weak.